2010
DOI: 10.1016/j.jinorgbio.2010.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh (0.93Å) resolution structure of manganese peroxidase from Phanerochaete chrysosporium: Implications for the catalytic mechanism

Abstract: Manganese peroxidase (MnP) is an extracellular heme enzyme produced by the lignin-degrading white-rot fungus Phanerochaete chrysosporium. MnP catalyzes the peroxide-dependent oxidation of MnII to MnIII. The MnIII is released from the enzyme in complex with oxalate, enabling the oxalate-MnIII complex to serve as a diffusible redox mediator capable of oxidizing lignin, especially under the mediation of unsaturated fatty acids. One heme propionate and the side chains of Glu35, Glu39 and Asp179 have been identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 59 publications
1
43
1
Order By: Relevance
“…Hydrophobic contacts were the leading interactions. It is worth noting that according to the crystal structure of MnP [77], the residues Glu35, Glu39 and Asp179 are also implied in the binding of Mn 2+ and the residue Arg42 could be involved in the stabilization of this ion through its interaction with Glu39. MD simulations of 3000 ps for this system were performed showing stability with respect to the starting conformation after 1000 ps, with a mean RMSD of 2.4 and 1.4 Å for the backbone of MnP and lignin, respectively.…”
Section: Manganese Peroxidasementioning
confidence: 99%
“…Hydrophobic contacts were the leading interactions. It is worth noting that according to the crystal structure of MnP [77], the residues Glu35, Glu39 and Asp179 are also implied in the binding of Mn 2+ and the residue Arg42 could be involved in the stabilization of this ion through its interaction with Glu39. MD simulations of 3000 ps for this system were performed showing stability with respect to the starting conformation after 1000 ps, with a mean RMSD of 2.4 and 1.4 Å for the backbone of MnP and lignin, respectively.…”
Section: Manganese Peroxidasementioning
confidence: 99%
“…(Timofeevski & Aust, 1997;Wariishi et al, 1992 (Aitken & Irvine, 1990). Active site and crystal structure analysis of P. chrysosporium MnP, the most studied MnP enzyme, have shown that arginine 42 and acidic amino acids (i.e glutamic or aspartic acid) at positions 35, 45, 39 and 179 are involved in Mn 2+ binding (Sundaramoorthy et al, 2010;Whitwam et al, 1997), while serine 172 seems to been involved in heme binding (AmbertBalay et al, 2000). MnP encoding genes have been cloned from several white-rot fungi strains, where up to three different genes have been reported each one encoding for a specific isoform (Alvarez et al, 2009;Martinez et al, 2009;Martinez et al, 2005).…”
Section: Manganese Peroxidasementioning
confidence: 99%
“…Peroxidases catalyse oxidation of a broad range of substrates by hydrogen hydroxide, so they may be successfully used for different industrial processes since peroxidases are capable of degrading aromatic rings in lignin, dyes, and polycyclic aromatic hydrocarbons [15,16,20,21]. In this sense, dyes are regarded as one of the most important contaminants to be removed from the industrial effluents, and peroxidases arise as a way to treat these pollutants.…”
Section: Introductionmentioning
confidence: 99%